PSYCHOLOGY AND LANGUAGE EDUCATION - Nelly safril; Neviyarni Neviyarni (Widyagogik, 2020)
ABSTRACTPsychology is the science of the soul, has a close relationship with language and analyzes language from the way humans behave and analyzes the potential that can be developed in mastering how to speak and communicate. One type of behavior that really distinguishes humans and animals is language, where humans need communication with fellow humans as a liaison, and the main link between humans is the way humans express their feelings and needs by language. Language connects an individual with other individuals, with human language understanding each other. On the other hand, the psychology of language education tries to find out a person's process in learning about language and how language can develop in individuals. The psychology of language education means revealing how a person learns to develop abilities in various aspects of language which is a means of communication. This article is designed to explain several problems, especially problems with the characteristics of language, issues in language and theories of language learning. As an introduction to language education that humans need in communicating and socializing with their social environment. As well as revealing things that support the development of language that is in humans. As an introduction to language education that humans need in communicating and socializing with their social environment. As well as revealing things that support the development of language that is in humans. As an introduction to language education that humans need in communicating and socializing with their social environment. As well as revealing things that support the development of language that is in humans.